Social Integration in Multiethnic and Multireligious Communities: A Socio-Cultural Analysis of Intergroup Relations in Makassar, Indonesia - Jamaluddin Arifin; Noor Insyiraah Abu Bakar; Rinaldi Rinaldi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study seeks to analyze the socio-cultural dynamics among multiethnic and religious communities within the Bosowa Indah housing area of Makassar city, with an emphasis on promoting social integration. Utilizing qualitative methods through a case study approach, data were gathered via direct observation, in-depth interviews, and documentation. The research focuses on social integration and socio-cultural relations, drawing upon theories grounded in functional structural paradigms, including Parsons' AGIL theory and Durkheim's concept of social solidarity, as well as symbolic interactionism and additional population theories. The findings indicate that Bosowa Indah is inhabited by a diverse urban population, with social interactions categorized into three types: formal interaction, informal interaction, and limited interaction. These interactions give rise to social and cultural products, reflected in established systems of values and norms, habits, and community practices that encourage social integration. Social integration is assessed through various dimensions: the establishment of trust among residents, the cultivation of shared values, cultural practices that foster a harmonious and peaceful society, and the development of a common identity. The results of this study offer significant theoretical insights for the advancement of sociology, particularly in the realm of urban sociology within a functional structural paradigm. Additionally, these findings can serve as a valuable reference for multiethnic community groups aiming to sustain social integration.